People who inject drugs remain hard-to-reach population across all HIV continuum stages in Central, Eastern and South Eastern Europe – data from Euro-guidelines in Central and Eastern Europe Network. Issue 4 (3rd April 2019) - Balayan, Tatevik; Oprea, Cristiana; Yurin, Oleg; Jevtovic, Djorde; Begovac, Josip; Lakatos, Botond; Sedlacek, Dalibor; Karpov, Igor; Horban, Andrzej; Kowalska, Justyna D.; ,
Abstract: Background/objectives : Inadequate HIV care for hard-to-reach populations may result in failing the UNAIDS 90–90–90 goal. Therefore, we aimed to review the HIV continuum of care and hard-to-reach populations for each step of the continuum in Central, Eastern and South Eastern Europe. Methods: Euro-guidelines in Central and Eastern Europe (ECEE) Network Group were created in February 2016. The aim of the network was to review the standards of HIV care in the countries of the region. Information about each stage of HIV continuum of care and hard-to-reach populations for each stage was collected through on-line surveys. Respondents were ECEE members chosen based on their expertise and involvement in national HIV care. Data sources (year 2016) used by respondents included HIV Clinics electronic databases, Institutes of Public Health, Centres for AIDS Prevention, and HIV Programme Reviews. Results: The percentage of people living with HIV (PLHIV) linked to HIV care after HIV diagnosis was ranged between 80% and 96% in Central Europe, 51% and 92% in Eastern Europe and 80% and 100% in South-Eastern Europe. The percentage of PLHIV who are on ART was ranged from 80% to 93% in Central Europe, 18% to 92% in Eastern Europe and 80% to 100% in South-Eastern Europe. The percentage of people virologically suppressed while on ART was reported as 70–95%, 12–95% and 62–97% in Central, Eastern, and South Eastern Europe, respectively. All three regions reported people who inject drugs (PWID) as hard-to-reach population across all HIV continuum stages. Migrants were the second most reported hard-to-reach population. The proportion of late presenters among newly diagnosed ranged between 20% and 55%, 40% and 55% and 48% and 60% in Central, Eastern and South Eastern Europe, respectively. Four countries reported ARVs' delivery delays resulting in treatment interruptions in 2016: two (25%) in South-Eastern, one (20%) in Central and 1 (16.7%) in Eastern Europe. Conclusion: Irrespective of the diversity in national HIV epidemics, countries from all three regions reported PWIDs as hard-to-reach population across all HIV continuum stages. Some countries are close to the UNAIDS 2020 goals, others need to strive for progress. However, differences in data sources and variations in definitions limit the utility of continuum of care as a comparative tool.